Endovascular intervention for iliac vein thrombosis after simultaneous kidney-pancreas transplant. Issue 4 (10th April 2019) - Gunder, Meredith; Lakhter, Vladimir; Lau, Kwan; Karhadkar, Sunil S; Di Carlo, Antonio; Bashir, Riyaz
Abstract: May–Thurner syndrome (MTS) is an anatomic variant where the overlying right common iliac artery compresses and chronically obstructs the left common iliac vein, leading to thrombosis. Interventions for symptomatic MTS include endovascular thrombectomy and stenting. Occluding venous thrombus can be fatal to transplanted allografts. No guidelines exist for patients with MTS after simultaneous kidney-pancreas transplant. A 57-year-old female with ESRD and diabetes mellitus underwent a kidney-pancreas transplant. Post-operative imaging revealed a compressed left CIV with an occlusive thrombus threatening the renal graft. Thrombectomy with stent placement was performed, maintaining patency of both allograft venous outflows. Post-intervention the patient has demonstrated preserved kidney and pancreas allograft function through 1 year of follow-up. Interventions for MTS in patients after transplant are challenging given the complex allograft vascular reconstruction. We present a case which demonstrates that angiographic interventions for MTS can be safely performed after simultaneous kidney-pancreas transplant.